Evaluation of pulse therapy with intravenous methylprednisolone on leprosy neuritis in a Brazilian referral center - Santos, Diogo Fernandes dos; Alves, Pedro Henrique Sirotheau Corrêa; Cirino, Fernanda de Oliveira; Garcia, Leonardo Peixoto; Fernandes, João Paulo Moreira; Antunes, Douglas Eulálio; Goulart, Isabela Maria Bernardes (Frontiers in Tropical Diseases, 2025)
BackgroundLeprosy neuritis (LN) is an immune hyperactivity majorly responsible for the deformities and sequelae present in leprosy disease. This observational study aimed to evaluate the use of intravenous methylprednisolone in refractory LN cases in a national reference center of leprosy in Brazil.MethodsEpidemiological and clinical data were collected, and the following instruments were used on evaluation: visual analog pain scale (VAS), Douler Neuropathic 4 questionnaire (DN4), Screening of Activity Limitation and Safety Awareness (SALSA), and the simplified neurological assessment protocol by the Brazilian Ministry of Health. The initial and final results of pulse therapy were compared.ResultsWe included 18 patients. After pulse therapy, there was no difference regarding sensory and motor scores. At the beginning of the treatment, 66.7% (12/18) of patients were using oral prednisone at 35.0 mg (± 12.43). After treatment, 38.9% (7/18) of them maintained oral prednisone at a lower dose (16.4mg ±6.3; p=0.002). Salsa score improved after treatment (p=0.020) and DN4 scores dropped from 6.7 (± 1.7) to 5.2 (± 2.1) (p<0.0001).ConclusionPulse therapy with endovenous methylprednisolone in LN was effective in decreasing pain intensity, preventing worsening of sensory-motor function, and reducing the dose of corticosteroids, reflecting the patient’s improvement of functionality.